2012
DOI: 10.1007/s00109-012-0883-2
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of mindin exacerbates cardiac hypertrophy and fibrosis

Abstract: Cardiac hypertrophy is a response of the myocardium to increased workload and is characterised by an increase of myocardial mass and an accumulation of extracellular matrix (ECM). As an ECM protein, an integrin ligand, and an angiogenesis inhibitor, all of which are key players in cardiac hypertrophy, mindin is an attractive target for therapeutic intervention to treat or prevent cardiac hypertrophy and heart failure. In this study, we investigated the role of mindin in cardiac hypertrophy using littermate Min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…1 and 4). This agrees with a recent report in which TRAF5 negatively regulates the ERK1/2 pathway in a model of cardiac hypertrophy (32). …”
Section: Discussionsupporting
confidence: 94%
“…1 and 4). This agrees with a recent report in which TRAF5 negatively regulates the ERK1/2 pathway in a model of cardiac hypertrophy (32). …”
Section: Discussionsupporting
confidence: 94%
“…237 Investigations by our laboratory have provided functional evidence that an ECM protein, Mindin, affects Ang II-or chronic pressure overload-induced cardiac hypertrophy. 238,239 In human failing hearts, the expression of Mindin is significantly decreased when compared with that in healthy controls. Because of the enhanced activation of AKT/GSK3β and TGF-β1/Smad signaling, cardiac remodeling induced by neuroendocrine factors or an illdefined mechanical stretch was dramatically exacerbated in Mindin-KO mice.…”
Section: Upstream Irf Signaling In Cardiac Remodelingmentioning
confidence: 99%
“…In this issue, Bian and colleagues [8] report on the role of mindin in cardiac hypertrophy. They relied on the mindin gene-deleted mouse model.…”
mentioning
confidence: 99%
“…The authors induced cardiac hypertrophy by thoracic aortic banding or angiotensin II (Ang II) infusion in mindin gene-deleted and wild-type mice. Bian et al found that mindin genedeleted mice were more susceptible to cardiac hypertrophy and fibrosis in response to thoracic aortic banding or Ang II stimulation than wild-type mice [8]. The mindin-deleted mice also had worsened cardiac function during both systole and diastole, compared to wild-type mice.…”
mentioning
confidence: 99%
See 1 more Smart Citation